Industrial training report: KS Healthcare (M) Sdn Bhd. Special project: Determinant of healthcare expenditure in Malaysia / Wan Zafirah Suhaila Mohamad - Mohamad, Wan Zafirah Suhaila (Universiti Teknologi MARA, Perlis, 2023)
KS Healthcare (M) Sdn. Bhd. is a young and vibrant company. It has been established in 2020. Their aim is to create an easy platform for people from all walks of life to enjoy quality medical attention. Their motto, "Mind That Cures, Heart That Cares". They provide a wide range of services, including simple house calls, routine home visits, in-depth workplace health and safety advice, and scheduled physiotherapy sessions. As of 2022, they are successfully managing five increasingly popular brands in Perak, Kuala Lumpur and Melaka. They think that data and technology will be the main forces in business in the future. Malaysia offers both public and private healthcare systems. To improve their service offers to medical travelers, private healthcare providers are encouraging the adoption of health technology and developing partnerships with foreign healthcare providers. Malaysia’s healthcare expenditures are expected to double to $2.8 billion by 2028. The general objective in this research is to determine the healthcare expenditures in Malaysia. The purpose of this study is to examine the income level, technology process and inflation on Malaysia healthcare expenditure. The data for this analysis was obtained from World Bank (WB) and OECD Statistics in the form of time series data spanning 30 years, from 1990 to 2020. In a nutshell, this study achieved the objective of finding out the relationship between independent variables and healthcare expenditure. The determinant of the independent variables, which include income level, inflation and technology process has been identified. Each variable has a significant impact on Malaysia healthcare expenditure, where income level is positively significant while the rest of the variables; inflation and technology process are negatively significant.